(untitled) (Revista Lusófona de Educação, 2026)
This essay explores the relationship between school architecture and pedagogy through the experience at the Green School in Bali, where the natural environment is central to the educational process. Drawing on direct observations and research, it examines how building design influences students’ autonomy, creativity, emotional regulation, and relationship with nature. The analysis highlights benefits such as stress reduction, promotion of physical activity and encouragement of pro-environmental behaviors, as well as challenges including acoustic isolation, environmental maintenance and safety. By connecting theory, pedagogical practice and architecture, the essay offers a critical reflection on how educational space supports students’ holistic development, suggesting new directions for innovative pedagogies and sustainable learning environments.